Historical Insight and Characteristic Culture Value of Historical Tour Guide in Japanese Tunnel Tourism Object - Naldi, Jefri; Fatimah, Siti (Science and Environmental Journal for Postgraduate, 2019)
Abstract This research was aimed to describe the historical insight and characteristic culture value of historical tour guide in Japanese Tunnel Panoramic Tourism Object. This research used qualitative method and ethnography approach. Purposive sampiling technique was used to select the informant with total number was 9 people. Data was collected by using method of interview, observation, and documentation. Intervew was conducted by applying indepth interview technique and observation was conducted by applying participant observation technique which object was examined in along period of time. Data was analyzed by using interactive analysis technique from Miles and Huberman (interactive analysis model) namely data reduction, data model, and conclusion. The result of this research showed that historical tour guide in Japanese Panoramic Tourism Object has had well historical insight (good). Such historical insight was obtained from written sources such as internet and history-related books. However, regarding competence and characteristic culture value, there was still no essential guiding elements such aslanguage skill; it was still difficult to serve foreign tourist. Professionalism (attitudes); humble manner, hospitality, politeness. Appearance (style); there has no identity badge (name tag) as a tour guide, and guiding technique; no interactive deliver for information thatleads to a dialogue which feedback was rarely given by both tour guide and tourist. Keywords; Culture value, historical insight, tour guide.